2000
DOI: 10.1159/000025752
|View full text |Cite
|
Sign up to set email alerts
|

Haemopoietic Origin of Myofibroblasts Formed in the Peritoneal Cavity in Response to a Foreign Body

Abstract: This study utilized both in vivo and in vitro techniques to investigate whether cells of bone marrow origin can differentiate into smooth muscle-like cells (myofibroblasts) with contractile filaments and proteins. Female C57BL/6 mice expressing the Ly5.2 antigen on the surface of their haemopoietic cells had four pieces of silastic tubing (3 × 0.5 mm outer diameter) or boiled blood clot (2–3 mm diameter) placed in their peritoneal cavity. After 3, 5, 7 and 14 days (n = 4/group) the implants were removed and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 7 publications
2
62
0
Order By: Relevance
“…These results confirm earlier electron microscopic studies, which reported the presence of cells intermediate in morphology between macrophage and fibroblast/myofibroblast within the tissue capsule 30 and provide evidence that the hematopoietic progenitor of the myofibroblast is the macrophage. 4 Macrophages have many trophic roles in development and are essential for effective tissue regeneration. 37 Although the role of macrophages was previously attributed to the paracrine production of cytokine/growth factors and extracellular matrix proteins to recruit and support other cell types, 2,38 the present study provides evidence for a more direct role in this process by way of their capacity to transdifferentiate into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results confirm earlier electron microscopic studies, which reported the presence of cells intermediate in morphology between macrophage and fibroblast/myofibroblast within the tissue capsule 30 and provide evidence that the hematopoietic progenitor of the myofibroblast is the macrophage. 4 Macrophages have many trophic roles in development and are essential for effective tissue regeneration. 37 Although the role of macrophages was previously attributed to the paracrine production of cytokine/growth factors and extracellular matrix proteins to recruit and support other cell types, 2,38 the present study provides evidence for a more direct role in this process by way of their capacity to transdifferentiate into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Given the prevalence of macrophages within the tissue capsule through to day 28, along with previous research showing the hematopoietic origin of capsular myofibroblasts, 4 we sought to determine whether cells of myeloid origin (ie, monocyte/macrophages expressing EGFP) within the tissue capsule can transdifferentiate into ␣-SM actin-expressing myofibroblasts. We reasoned that such cells would retain the stable EGFP protein even if transcription of macrophage-specific genes was extinguished.…”
Section: Macrophage Transdifferentiation Into Tissue Capsule Myofibromentioning
confidence: 99%
See 2 more Smart Citations
“…The other marker, CD18, suggests that these intimal cells may indeed be derived from leukocytes, either as a direct result of blood perfusion or as part of the foreign body reaction, as suggested by both the Campbell and Cebotari groups. 3 In any case, this mixed phenotype is indicative of a transdifferentiation process, which may be further stimulated 4,5 and exploited.…”
Section: To the Editormentioning
confidence: 99%